Burden of psoriasis in young adults worldwide from the global burden of disease study 2019 - Zhang, Yuanchen; Dong, Shuai; Ma, Yuan; Mou, Yan (Frontiers in Endocrinology, 2024)
Background: To determine the global burden of psoriasis in young adults, i.e., those aged 15-49, from 1990 to 2019 and predict trends in this burden for 2020 to 2030.Methods: Age-standardized disease burden indicators and their estimated annual percentage changes were assessed and used to compare the estimated burden between regions. In addition, generalized additive models were used to predict the burden in this population from 2020 to 2030.From 1990 to 2019, the overall burden of psoriasis in young adults worldwide trended downward, as the age-standardized incidence rate and the age-standardized disability-adjusted life year rate decreased. From 1990 to 2019, there were gender differences in the burden of psoriasis between regions with different Socio-demographic index. Specifically, there was a smaller increase in the burden in young men than in young women in middle-and low-middle-Socio-demographic index areas. In 2019, Western Europe, Australasia, and Southern Latin America had the highest agestandardized incidence rate of psoriasis in young adults, whereas age-standardized disability-adjusted life year rates of psoriasis in young adults were highest in high-income North America. In 2019, the psoriasis burden in young adults was the highest in high-Socio-demographic index areas and the lowest in low-Socio-demographic index regions. We predict that from 2020 to 2030, the incidence rate and disability-adjusted life year rate of psoriasis in all age groups of young adults will continue to decline, but the burden in those aged 30-39 will increase.From 1990 to 2019, the overall burden of psoriasis in each age group trended downward in this period. We predict that from 2020 to 2030, the burden of psoriasis in those aged 30-39 will increase.